AESTHETIC SENSIBILITY IN THE WORLD OF POLITICS - Buhre, Frida (The Nordic Journal of Aesthetics, 2022)
Review of CECILIA SJÖHOLM: ATT SE SAKER MED ARENDT: KONST, ESTETIK, POLITIK GÖTEBORG: DAIDALOS, 2020. 248 PAGES ISBN: 9789171735461